GLP-1 receptor agonists: exploration of transformation from metabolic regulation to multi-organ therapy - Gong, Bing; Li, Couwen; Shi, Zhuang’e; Wang, FuPing; Dai, Ruanxian; Chen, Guobing; Su, Heng (Frontiers in Pharmacology, 2025)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs), initially developed for type 2 diabetes and obesity, have evolved into multi-organ potential therapeutics due to their pleiotropic effects beyond glycemic control. Mechanistically, GLP-1 signaling modulates immune and inflammatory pathways, regulates autophagy and pyroptosis, alleviates endoplasmic reticulum stress, and interacts with the gut microbiome. These pleiotropic effects provide a rationale for exploring their role in multiple organ systems. Clinical trials have demonstrated cardiovascular and renal protection, leading to additional approvals in high-risk populations. Early data also suggest potential benefits in liver disease, obstructive sleep apnea, chronic respiratory disorders, neurodegenerative and psychiatric conditions, reproductive dysfunction, obesity-associated cancers, and sepsis, although these remain investigational. Therefore, this review aims to synthesize the evidence on the mechanistic expansion of GLP-1RAs from metabolic regulators to systemic modulators of inflammation, autophagy, and organ protection, and explores their therapeutic repurposing across diseases.